1985
DOI: 10.1073/pnas.82.9.2693
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor-mediated recognition of maleyl bovine plasma albumin and the demaleylated protein in human monocyte macrophages.

Abstract: Maleyl bovine plasma albumin competed on an equimolar basis with malondialdehyde low density lipoprotein (LDL) in suppressing the lysosomal hydrolysis of 251-labeled malondialdehyde LDL mediated by the scavenger receptor of human monocyte macrophages. Maleyl bovine plasma albumin, in which 94% of the amino groups were modified, exhibited an anodic mobility in agarose electrophoresis 1.7 times that of the native protein. Incubation of maleyl bovine plasma albumin at pH 3.5 regenerated the free amino groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 32 publications
5
59
0
Order By: Relevance
“…In vitro assays confirmed that the absence of receptors did not affect AM binding of OVA, as doubledeficient AMs bound Alexa-OVA to nearly the same extent as did control AMs (data not shown). These findings are consistent with previous reports indicating that, unlike chemically modified albumin, native albumin binding to MΦs is not mediated through SRAs (17)(18)(19), and also indicate that nebulization does not per se denature the allergenic proteins sufficiently to create SRA-binding domains.…”
Section: Wt and Sra-deficient Lung Mφs Show Normal Uptake Of Inhaled supporting
confidence: 82%
See 1 more Smart Citation
“…In vitro assays confirmed that the absence of receptors did not affect AM binding of OVA, as doubledeficient AMs bound Alexa-OVA to nearly the same extent as did control AMs (data not shown). These findings are consistent with previous reports indicating that, unlike chemically modified albumin, native albumin binding to MΦs is not mediated through SRAs (17)(18)(19), and also indicate that nebulization does not per se denature the allergenic proteins sufficiently to create SRA-binding domains.…”
Section: Wt and Sra-deficient Lung Mφs Show Normal Uptake Of Inhaled supporting
confidence: 82%
“…AMs can efficiently bind and internalize unopsonized particles and bacteria through SRAs, leading to the clearance of inhaled matter from the airways and the reduction of the resulting inflammation (7-9), and are known to similarly bind modified proteins (17)(18)(19). To determine if SRAs could reduce allergic inflammation by simply 'scavenging' aeroallergen with a resulting decrease in allergen dose, we measured their ability to internalize inhaled allergens using FITC-OVA.…”
Section: Wt and Sra-deficient Lung Mφs Show Normal Uptake Of Inhaled mentioning
confidence: 99%
“…Probes for endocytosis and immunodetection mBSA was prepared as described earlier (Haberland and Fogelman, 1985). Fluorescent conjugates were made according to the instructions provided by the manufacturer with minor modifications.…”
Section: Cell Culturementioning
confidence: 99%
“…In addition to maleylated proteins, SRs bind to many other ligands (31)(32)(33)40), and we have shown previously that SR-like binding capabilities are exhibited by all professional APCs (35), although classical SRs are known to be present only on cells of the monocytic lineage (31,33,34). To examine the role of macrophages in presentation of self-Ags to generate autoimmune responses, we used CGN to deplete macrophages of their functional capability at the time of immunization.…”
Section: Targeting Of Ags To Scavenger Receptors In Vivo Is Crucial Fmentioning
confidence: 99%
“…For this purpose, we have used maleylated self-Ags. Protein maleylation confers on them the ability to bind to scavenger receptors (SRs) 3 (31)(32)(33). Although classical SRs are restricted to cells of the monocytic lineage such as macrophages and dendritic cells (DCs) (33,34), other receptor molecules with the ability to bind SR ligands have also been shown to be present on B cells (34,35).…”
mentioning
confidence: 99%